Influence of Surfactant Concentration and Temperature Gradients on Spreading of Crude-Oil at Sea* - Boniewicz-Szmyt, Katarzyna; Pogorzelski, Stanisław Józef (Frontiers in Marine Science, 2018)
Spreading kinetics measurements were carried out on crude oils at natural surfactant-containing sea water of well-controlled thermo elastic surface properties in laboratory conditions. It was found that oil lens expansion rates, predicted from the classical surface tension-driven spreading theory, were higher by a factor of 6-9 than those experimentally derived for natural seawater. Previously, in order to explain such a discrepancy, the initial spreading coefficient S0 - entering the lens radius vs time dependence was exchanged with the temporal one St dependent on the water phase surface viscoelasticity of (Boniewicz and Pogorzelski, 2008). Now, natural surfactant concentration and temperature gradients perpendicular to the surface were shown to drive a particular cell-like flow at the surface microlayer, as a result of the classic and thermal Marangoni phenomenon. The balance of interfacial forces was taken as: -µ∂Us/∂z=∂γ/∂T•∂T/∂x+∂γ/∂c•∂c/∂x where: µ is the dynamic viscosity, Us - the velocity, z and x axes oriented perpendicularly and horizontally to the main flow direction, T, γ, c are the temperature, surface tension and concentration of surfactants. Computations performed on original seawater (Baltic Sea) systems, shown that the natural surfactant concentration term ∂γ/∂c is several times lower than the thermal ∂γ/∂T one (Boniewicz and Pogorzelski, 2016). Such a surface tension gradients induce the Benard-Marangoni instability, for high enough the so-called Marangoni numbers that could significantly slow down the spreading process. On the basis of thermo-physical model liquids properties, the critical temperature difference ∆Tc required to initiate the process under an evaporative cooling condition was evaluated.